The surprising capacity of the company you keep: Revealing group cohesion as a powerful factor of team production - Simon Gächter; Chris Starmer; Fabio Tufano (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2019)
We introduce the concept of "group cohesion" to study the economic consequences of social relationships in team production. We measure group cohesion, adapting the "oneness scale" from psychology to group level. A series of experiments, including a pre-registered replication, reveals that higher cohesion groups are more likely to achieve Pareto-superior outcomes in weaklink coordination games. Judged against benchmarks, the effects of cohesion are economically large. We identify beliefs rather than social preferences as a primary mechanism explaining the effects of cohesion. Our comprehensive evidence establishes group cohesion as a powerful production factor and a useful new tool of economic research.
Keywords: C92; D03; 330